Effects of species mixing on maximum size–density relationships in Chinese fir (Cunninghamia lanceolata (Lamb.) Hook.)-dominated mixed forests converted from even-aged pure stands - Han, Yuanyuan; Wang, Baichang; Sun, Honggang (Frontiers in Plant Science, 2024)
Density management is a key silvicultural tool in management programs that enhances compositional and structural diversity and hence forest growth during the conversion of even-aged pure stands into mixed forests. To determine the optimum stand density, a model of maximum size-density relationships was employed to explore the relationship of the self-thinning trajectory with growth, species mixing, latitude, and site conditions during the transition of even-aged pure Chinese fir stands to Chinese firdominated mixed forests using stochastic frontier analysis. Data were obtained from a total of 591 permanent plots located in Fujian, Jiangxi, Zhejiang, and Anhui provinces in southern China. The results showed that (1) the slope of the maximum size-density relationship of Chinese fir-dominated mixed forests increased and plateaued over time;(2) the slope of the maximum size-density relationship of Chinese fir-dominated mixed forests did not deviate from Reineke's assumed universal slope of -1.605; and (3) mixing proportion had a positive effect on maximum size-density relationships, and latitude and site conditions had the opposite effect on maximum size-density relationships. Our findings will provide valuable guidance for the forest management of areas in which even-aged pure stands are being converted to mixed forests (i.e., when broadleaved tree species are planted after thinning to improve overall stand density and promote stand growth).